Perceived usefulness, ease of use and attitude as predictors of behavioral to use the UAE-TIR AI system in the Federal Authority of Identity and Citizenship of UAE - Abdalla Yousif Al Yassi, Abdalla Yousif (2025)
Artificial intelligence (AI) has changed the work in modern organizations around the globe. In the United Arab Emirates (UAE), government policies on AI and its associated strategies have gradually regulated AI usage in public service. Thus, the Federal Authority for Identity, Citizenship, Customs & Port Security (ICP) have also adjusted their operation in parallel to the National Artificial Intelligence Strategy 2031. The aim of this study is to investigate the acceptance of employees of ICP to adopt AITIR system through Technology Acceptance Model (TAM). This study adopted quantitative research methodology by conducting surveys with random sampling techniques. Then, SPSS and AMOS were thoroughly used for data analysis alongside the analysis of data from secondary sources. The results revealed significant relationships among the perceived usefulness and ease of use of AI, attitude towards using AI, behavioral intention to use AI, and actual use of AI in ICP. By understanding the factors that influence users' acceptance of AI systems, researchers and developers can design more user-friendly and effective AI solutions. To that end, studying the TAM model in the AI domain can help identify potential barriers to adoption and inform strategies for overcoming them. This study recommends practical benefits of AI adoption in customs operations and emphasizes on the ability of AI to streamline processes, improve accuracy, and enhance security measures. This study also highlights concrete examples that demonstrate the usefulness of AI in public service organization of UAE.